مقاربات مفهوم الجمال في قول السيدة زينب (ع) (ما رأيت الا جميل) دراسة تجريبية: مقاربات مفهوم الجمال في قول السيدة زينب (ع) (ما رأيت الا جميل) دراسة تجريبية - alasady, علي حسين (Basrah Arts Journal, 2025)
Abstract: The study included five chapters that began with the introduction, which included : the problem of research and then its importance, and then the researcher formulated three goals to achieve the title of the research and then determined the limits of his study and then defined the beautiful linguistically, idiomatically and procedurally, after that he included the literature of his research through four investigations, and the researcher did not find a previous published research study. As for the researcher's procedures, they are experimental related to the art of painting, as the research community included the same experimental models, numbering five paintings, whose ideas were derived from the approaches to the saying of Sayyida Zeinab (I saw nothing but beautiful) From the results: 1-The beautiful comes from the mental essence of belief, while its aesthetic impact is deduced for Sayyida Zeinab (pbuh) from the past of Al-Hussein (pbuh), his present and the future status of his testimony. 2-The beautiful is an existential necessity as an energy of attraction that Allah has singled out for his creatures, no matter how cruel the existence is. From the conclusions: 1-The research revealed that the beauty Husseini can be expressed in a variety of artistic media. 2-The study showed that the beautiful on two places apparent and essential and deductive judgment of the abundance of knowledge. Keywords: Hussein (pbuh), Sayyida Zeinab (pbuh), Battle of Karbala, Beauty, Experimental Painting Art.